Multifocal Osteolytic tuberculosis - Uncommon presentation of common disease - Majed B Momin1 , Sandeep S2 , Anamika Aluri3 , Akhhil M4 (Perspectives In Medical Research, 2018)
Tuberculosis is one of the most prevalent bacterial infection in developing country like india and it is capable of affecting almost every system in the human body. Multifocal skeletal tuberculosis is a rare condition. We report a 22-year old immunocompetent female history of backache and sternal pain for three months, associated with progressive weight loss with no fever. Computed Tomography (CT) scanning demonstrated hypodense multifocal osteolytic lesions of the thoracic spine (T12) and the manubrum sternii. CT guided fine needle aspiration cytology (FNAC) performed from both osteolytic lesions. Cytology smears from both lesions show many granulomas and few giant cells. Z-N stain for AFB was positive. Patient treated with anti-tuberculus drugs and responded well. This case reported for its rarity, unusual radiological findings & to emphasize the role of CT/CT guided FNAC in osteolytic lesions and also to stress the need for high index of suspicion in tuberculosis endemic areas to avoid delayed diagnosis in such uncommon presentation of common disease.